2015
DOI: 10.5489/cuaj.2697
|View full text |Cite
|
Sign up to set email alerts
|

Impact of drainage technique on pediatric pyeloplasty: Comparative analysis of externalized uretero-pyelostomy versus double-J internal stents

Abstract: Introduction: Pediatric pyeloplasty with double J (DJ) stent drainage requires manipulation of the uretero-vesical junction (UVJ) and a second anesthetic for removal. Externalized uretero-pyelostomy (EUP) stents avoid these issues. We report outcomes of laparoscopic and open pyeloplasty with EUP compared to DJ stents in children. Methods: We retrospectively reviewed 76 consecutive children who underwent pyeloplasty for ureteropelvic junction (UPJ) obstruction over a 1-year period by 5 pediatric urologists at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 19 publications
2
25
2
Order By: Relevance
“…One report suggested that there were fewer complications with the use of a percutaneous transanastomotic stent ( 13 ), but in others, the results were similar or better compared with JJ stent ( 16 ). In our series with retrograde placement of the JJ stent after a retrograde pyelogram, there have been no stent-related postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…One report suggested that there were fewer complications with the use of a percutaneous transanastomotic stent ( 13 ), but in others, the results were similar or better compared with JJ stent ( 16 ). In our series with retrograde placement of the JJ stent after a retrograde pyelogram, there have been no stent-related postoperative complications.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested, that DJS use during robotic reconstructive surgery, might lower the rate of post-operative leaks and obstruction by maintaining an appropriate ureteral diameter and prevent adhesions or kinking of the suture line. Furthermore, stenting may prevent transient obstruction by blood clots or edema at the anastomotic site [3,6,8,16,20]. One might believe that a smaller stent, with narrower lumen such as the 3Fr DJS, would be more prone to obstruction and thus to anastomotic leak or hydronephrosis aggravation.…”
Section: Discussionmentioning
confidence: 99%
“…In the past few decades, less invasive laparoscopic and robot-assisted laparoscopic approaches have become more widely used in reconstructive ureteral procedures among the pediatric population [1]. Placement of an indwelling ureteral DJS at the time of the procedure has both its advocates and detractors, with different outcomes reported in several studies, ranging from lowered morbidity and shortened hospital stay to stent failure and the need for a redo operation [2][3][4][5][6][7][8]. The diameter of DJS as a predicament to its failure or success, has not been addressed in most studies.…”
Section: Introductionmentioning
confidence: 99%
“…18 Cost of stent, second anesthesia, early discharge, urinary leak, infections and anastomotic stricture will determine use of the stent. 11,12,19 However prospective double blind random study of pyeloplasty on stent or stent less may be needed. Post pyeloplasty EC scan showed 5-10% renal function recovery.…”
Section: -13mentioning
confidence: 99%